2020
DOI: 10.1002/jbm.a.36889
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing biodegradable tissue engineering scaffolds for localized chemotherapeutic delivery

Abstract: While highly porous biodegradable sponges have typically been used as tissue engineering scaffolds, they could be applicable in settings requiring drug delivery. Since most drug delivery devices are intentionally solid, nonporous polymers, a detailed structure–function relationship of delivery from a porous degradable sponges would allow researchers to develop such devices for either delivery alone, or in conjunction with tissue engineering. Two fabrication techniques (salt‐leaching and solvent‐quenching) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…RIF release quickly reached a plateau from the microparticles, yet the β-CD disk continued to sustain RIF release until day 30. With the β-cyclodextrin disks utilized in this study, the molecular weight and hydrophobicity of the drugs were found to correlate more closely with loading efficiency (Pearson correlation coefficients of r = −0.761 and r = −0.555, respectively [40]) than the affinity measurements (correlation coefficient of r = −0.390). Binding affinity correlated more with drug release rate from cyclodextrin-based polymers (r = −0.283) than molecular weight with release rate (r = −0.145), while solubility maintained a larger effect on the release half-life (r = −0.490).…”
Section: Drug-polymer Characteristics Juxtaposed With Release Datamentioning
confidence: 84%
“…RIF release quickly reached a plateau from the microparticles, yet the β-CD disk continued to sustain RIF release until day 30. With the β-cyclodextrin disks utilized in this study, the molecular weight and hydrophobicity of the drugs were found to correlate more closely with loading efficiency (Pearson correlation coefficients of r = −0.761 and r = −0.555, respectively [40]) than the affinity measurements (correlation coefficient of r = −0.390). Binding affinity correlated more with drug release rate from cyclodextrin-based polymers (r = −0.283) than molecular weight with release rate (r = −0.145), while solubility maintained a larger effect on the release half-life (r = −0.490).…”
Section: Drug-polymer Characteristics Juxtaposed With Release Datamentioning
confidence: 84%
“…In previous in vivo experiments, differences were demonstrated in the IM characteristics with regards to TNFα, VEGF and BMP expression between coated and non-coated BAG-S53P4 scaffolds without any obvious deleterious effects (Björkenheim et al, 2017;Björkenheim et al, 2019). The rationale behind the rapid degradation profile of the utilised PLGAminimum of 14 d (Cyphert et al, 2020) -was to allow the BAG-S53P4 to interact with the surroundings as early as possible to hinder the formation of a fibrotic capsule. These findings were hypothesised to be due to a stronger initial inflammatory reaction of PLGAcoated scaffolds compared to uncoated BAG-S53P4 scaffolds alone, leading to a formation of a biologically more active IM.…”
Section: Discussionmentioning
confidence: 99%
“…Designated BAG scaffolds were dip coated with an acid-terminated PLGA called PDLG5002A at a 50 : 50 ratio between DL-lactide and glycolide (Corbion, Gorinchem, the Netherlands). The theoretical minimum degradation time of the utilised PLGA is 14 d (Cyphert et al, 2020). After coating, the BAG-S53P4-PLGA scaffolds were dried in air and vacuum.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations